China’s Role In Indonesia's “Crush Malaysia” Campaign - Dahana, A (Makara Human Behavior Studies in Asia, 2002)
This paper argues that contrary to the traditionally accepted opinion, the People’s Republic of China (PRC) participated in the Indonesian campaign to crush Malaysia half-heartedly. In fact, despite its strong propaganda broadcast in supporting Indonesia, the PRC was actually a passive participant in the campaign. This is due to the fact that at that time the Chinese supported Malayan Communist Party, which was pursuing a more conciliatory policy toward the Malaysian government. Furthermore, China was probably more concerned with the well-being of ethnic Chinese Malaysia than supporting the local communist party.